The Temnocephalidae (Platyhelminthes): molecular data illuminate the evolution of an ancient group of symbiotic flatworms. Issue 1 (31st December 2023) - Blair, David; Cannon, Lester R.G.; Littlewood, D. Timothy J.; Olson, Peter D.; Sewell, Kim B.
Abstract : The Temnocephalidae sensu Van Steenkiste et al., 2021 is a diverse group of rhabdocoel flatworms that are ectosymbiotic mostly on freshwater crustaceans. The family is found on all inhabited continents except for N. America (north of Mexico) and Africa. Here, we explore the systematic implications of a molecular phylogeny inferred from partial sequences of the nuclear 18S and 28S ribosomal RNA genes. In agreement with previous views based on morphology, the earliest diverging group within the family was exemplified by the genus Scutariella (subfamily Scutariellinae) followed by the genus Didymorchis (Didymorchinae). The genus Dactylocephala from Madagascar, previously thought to be in the Temnocephalinae, then diverged as sister to the remaining temnocephalids. A new subfamily, Dactylocephalinae, is proposed to contain this genus. Remaining subfamilies were, in turn, Diceratocephalinae, Actinodactylellinae and Temnocephalinae. Further subdivision was apparent within the Temnocephalinae. One well-supported clade included the genera Temnohaswellia (eastern Australia and New Zealand), Temnomonticellia (Tasmania) and Temnocephala (South America). The widespread genus Temnosewellia (= Ts. ) was not supported as monophyletic. One clade of Temnosewellia sensu lato included numerous species known primarily from crayfish of the genus Euastacus, found in eastern and south-eastern Australia. Two other clades circumscribed the taxa Ts. minor and Ts. dendyi . Identities and membership of these two clades are clouded by frequent misidentifications, the reasons for which are discussed here. A fourth clade of Temnosewellia s.l. included Ts. rouxi and other taxa from northern Australia and Asia (ranging at least from Japan to India). The diversity of temnocephalids in Australia, and especially in Asia, is greatly underappreciated. Some general comments are made about geographic distribution of temnocephalids, but detailed biogeographic analysis requires broader sampling. http://zoobank.org/urn:lsid:zoobank.org:pub:C8E6F83E-5A8E-4756-AAB9-1E65BBA7D9DE